Relationship Between Uptake of Antenatal Care Services and Low Birth Weight in the Gushegu District of Northern Ghana - Saaka, Mahama; Rauf, Abdulai Abdul (International Journal of Child Health and Nutrition, 2013)
<!– [if gte mso 9]> <![endif]–> Objective: Little is known about the relative contribution of prenatal care utilization on pregnancy outcome in developing country setting where other equally important predictors of low birth weight (LBW) including malarial infection and poor diet predominate. This study investigated whether the utilization of antenatal care (ANC) services is an independent predictor of LBW in Northern Ghana. Methods: In this community based cross sectional study, we compared pregnancy outcome (birth weight) across groups of 407 women who received different amounts of ANC. Results: The incidence of low birth weight (LBW) of newborn babies was 18.2 % (74/407). The main finding was that women who made at least four ANC visits had 63.0 % protection against delivering a LBW (AOR = 0.37, 95 % CI: 0.19, 0.69). Conclusion: The results of this study suggest that adequate antenatal care is effective in preventing LBW in a rural setting but its effect was more discernible among women who were not in gainful employment (suggestive of low socio-economic status). <!–[endif] –>